Porto de Vitória : armazéns do século XX patrimônio industrial e memória do trabalho - Morais, Lívia Santos de (2014)
This dissertation discusses the history of the Espírito Santo in parallel with the history about port of Vitória, aiming thereby to encourage and stimulate the study of capixaba culture. For this, a survey was done in secondary source of the colonial Braz